Fooling the user? Modding in the video game industry - Merlin Münch (Internet Policy Review, 2013)
Over the years, the video game industry has grown into one of the largest, most profitable entertainment industries in the world. In a highly competitive industry, legal difficulties to safeguard successful game concepts from copycats contribute to a trend of risk aversion and reliance on established game franchises. It does not come as a surprise then, that user-driven innovation, or 'modding', has come to play a considerably important role for the industry in recent years. While modders are becoming increasingly aware of the financial weight of their activities, game companies seek to secure the legal ownership of the content they create. By means of a literature review this article seeks to investigate the ongoing juridification of the relationship between modders and the industry, in order to provide a brief insight into the complex of intellectual property in relation to user generated content and the tensions that arise due to a mesh of messy legal and social arrangements.
Keywords: 300; Innovation; Game development; User-generated content; Modding; Copyright; Intellectual property; Video games; Games